The midwife said “It’s okay” – a qualitative study on the causes of delayed retinoblastoma treatment - Darajati, Irene Titin; Sulistyoningrum, Evy; Wardhani, Yulia; Supriyati, Endah; Maharani, Erika; Kurniawati, Herlin Fitriana; Panggabean, Andre Stefanus; Aulia, Afkar; Muttaqqin, Habib Zahar Zaki; Puspitawati, Ira; Supriyati, Supriyati (BKM Public Health and Community Medicine, 2025)
Purpose: Retinoblastoma is the most common primary intraocular tumour in children. Its prognosis varies depending on the stage of diagnosis. However, in developing countries such as Indonesia, retinoblastoma still has a poor prognosis as most patients present at advanced stages. This research aims to explore the factors influencing the delay in patients with retinoblastoma reaching referral health facilities from the perspective of their families. Methods: A qualitative study using a phenomenological approach was conducted to gather family perspectives through in-depth interviews via WhatsApp calls. Each interview lasted 20-25 minutes and included families of retinoblastoma patients who had visited the eye clinic at Sardjito General Hospital at a late hour. “Late” was defined as tumour spread beyond the eyeball (intraorbital, spread to the optic nerve, or intracranial spread) or involvement of more than one eye. Audio was transcribed verbatim using a mobile phone voice recorder, and open coding was performed using Open Code 4.02 software to identify meaning units, codes, and categories. Triangulation and peer debriefing were used to ensure validity and trustworthiness. Results: Several categories emerged, including reasons for seeking help, trust in medical professionals, family compassion, and challenges in health facilities. Challenges in health facilities, particularly diagnostic capabilities, communication, and education about eye tumours, along with negative emotions like denial from families, contributed to delays in seeking treatment for retinoblastoma patients. Conclusion: Family compassion plays a positive role in encouraging families to seek medical help. However, challenges in health facilities, particularly in diagnosis, communication, and education about eye tumors, as well as family denial, contribute to the delays in retinoblastoma patients reaching referral health facilities.